The Influence of Environmental, Social and Governance (ESG) on Debt Costs in Companies Energy Sectors Listed on the IDX - Nurul Nurul; Ari Agung Nugroho; Darman Saputra (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2026)
This study aims to examine the Effect of Environmental, Social, and Governance (ESG) on the Cost of Debt in Energy Sector Companies Listed on the IDX "The population in this study uses all energy sector companies listed on the Indonesia Stock Exchange. The following is a list of 87 energy sector companies listed on the IDX in 2024. Data analysis in this study uses the panel data regression analysis method with the help of EViews version 13 statistical software. This software was chosen because of its superior capabilities in handling panel data, statistical testing, and interpretation of regression results. The results of the study show that environmental (EVM) and Social (SCL) have a negative and significant effect on the Cost of Debt in energy sector companies listed on the Indonesia Stock Exchange in 2020-2024. Governance (GVN) has a positive and significant effect on the Cost of Debt in energy sector companies listed on the Indonesia Stock Exchange in 2020-2024.